PROSPECTS FOR USING COMBINED UNITS IN AGRICULTURE - Sobirov Rasulbek Vakhobovich (European Science Publishing, 2023)
It is known that tillage is one of the main activities in the cultivation of agricultural crops. Cultivated soil differs from ordinary soil in its composition, hardness, content of humus content, i.e. fertility [1]. Agricultural machines work only on fertile soil.